(untitled) (Bangladesh Journal of Medical Science, 2017)
Background: Weight status perception associates with objective weight status and is important in the management of weight control. To date, perception of weight status among Indonesian youths has not been reported. Objectives: This study aimed to examine the association between body mass index and weight status perception in a sample of college students in Yogyakarta Province. Materials and Methods: A sample of 209 boys and 269 girls of college students in Yogyakarta Province were measured for their stature and body weight. Body mass index was calculated (BMI). Data of demographic, exercise, and diet were collected. Weight status perception was based on participant responses to a question regarding how they classified their own body size as underweight, normal, overweight, or obese. Ordinal regression analysis was performed to evaluate factors associated with weight status misperception among boys and girls. Results: Overall, 43.5% of boys and 37.5% of girls misclassified their own weight status by actual BMI. Of particular note, 75.9% of obese boys and 78.6% of obese girls underestimated their weight status as overweight or normal weight. Whereas, 9.1% and 23.4% of normal weight boys and girls respectively, overestimated their weight status. Ordinal regression analysis revealed that, weight status misperception from others was significantly contributed (p<0.01) to misperception of weight status among boys and girls with OR of 10.31 and 8.13 respectively. Diet practicing was significantly correlated with weight status misperception in boys (p<0.05) with an OR of 19.57. Conclusions: Weight status misperception was prevalent among normal weight and obese students. Obese students of both gender and normal weight boys tended to underestimate their weight status, whereas normal weight girls were likely to overestimate their weight status. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.225-232